Shear Stress Ameliorates Superoxide Impairment to Erythrocyte Deformability With Concurrent Nitric Oxide Synthase Activation - Kuck, Lennart; Grau, Marijke; Bloch, Wilhelm; Simmonds, Michael J. (Frontiers in Physiology, 2019)
The cellular deformability of red blood cells (RBC) is exceptional among mammalian cells and facilitates nutrient delivery throughout the microcirculation; however, this physical property is negatively impacted by oxidative stress. It remains unresolved whether the molecular determinants of cellular deformability – which in the contemporary model of RBC are increasingly recognized – are sensitive to free radicals. Moreover, given cellular deformability has recently been demonstrated to increase following exposure to specific doses of mechanical stimulation, the potential for using shear “conditioning” to reverse free-radical induced impairment of cell mechanics is of interest. We thus designed a series of experiments that explored the effects of intracellular superoxide (O2-) generation on the deformability of RBC and also activation of pivotal molecular pathways known to regulate cell mechanics – i.e., PI3K/Akt kinase and RBC nitric oxide synthase (NOS). In addition, RBC exposed to O2- were conditioned with specific shear stresses, prior to evaluation of cellular deformability and activation of PI3K/Akt kinase and RBC-NOS. Intracellular generation of O2- decreased phosphorylation of RBC-NOS at its primary activation site (Ser1177) (p < 0.001), while phosphorylation of Akt kinase at its active residue (Ser473) was also diminished (p < 0.001). Inactivation of these enzymes following O2- exposure occurred in tandem with decreased RBC deformability. Shear conditioning significantly improved cellular deformability, even in RBC previously exposed to O2-. The improvement in cellular deformability may have been the result of enhanced molecular signaling, given RBC-NOS phosphorylation in RBC exposed to O2- was restored following shear conditioning. Impaired RBC deformability induced by intracellular O2- may be due, in part, to impaired activation of PI3K/Akt, and downstream signaling with RBC-NOS.